Development of an enzymatic biosensor based on a boron-doped diamond surface - Tavares, Bernardo Loureiro (2023)
Biosensors are innovative technologies that have great potential over currently used detection methods. Enzymatic biosensors have been used as innovative detection platforms in search of personalized strategies, as they possess the robustness of electrochemical techniques and specificity of biological recognition processes. They offer many advantages due to their reduced size, cost, high sensitivity, selectivity, and fast response. In this work, an electrochemical boron-doped diamond sensor was developed to detect enzymatic reactions using Laccase (oxidative enzyme) and Asparaginase (non-oxidative enzyme). The boron-doped diamond sensor was developed using HFCVD and enzymatic assays were performed to evaluate the capability of the electrochemical sensor based on boron-doped diamond as an amperometric electrochemical sensor for real-time quantification of Laccase and Asparaginase activity. The primary objectives of this work were the fabrication and optimization of the boron-doped diamond sensors, followed by performing enzymatic assays for comparison with currently used methods. The development of the diamond sensor and measuring system was successful and only a Laccase calibration curve in the range of 0.15 – 1.00 mg/mL was obtained, whereas ASNase didn’t demonstrate a readable signal for precise measurement. Future work should focus a detection strategy recurring to voltammetry, downsizing the measurement system and apply the measurement system to immobilized enzymes.